The Key Role of RNA Modification in Breast Cancer - Liu, Yang; Zhu, Tong; Jiang, Yi; Bu, Jiawen; Zhu, Xudong; Gu, Xi (Frontiers in Cell and Developmental Biology, 2022)
The modulation of the function and expression of epigenetic regulators of RNA modification has gradually become the hotspot of cancer research. Studies have shown that alteration of epigenetic modifications can promote the development and metastasis of breast cancer. This review highlights the progress in characterization of the link between RNA modification and the prognosis, carcinogenesis and treatment of breast cancer, which may provide a new theoretical basis for development of effective strategies for monitoring of breast cancer based on epigenetics.